2018
DOI: 10.1111/cid.12616
|View full text |Cite
|
Sign up to set email alerts
|

Dento‐alveolar measurements and histomorphometric parameters of maxillary and mandibular first molars, using micro‐CT

Abstract: Using micro-CT, three-dimensional aspects of the human first molar morphology and microstructural parameters of the surrounding bone were evaluated in the mandible and in the maxilla. These comprehensive measurements and their correlation with aging may be of great importance for the use of immediate implant placement in molar extraction sockets and thus the potential long-term success of this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
0
12
0
3
Order By: Relevance
“…Most of the afore mentioned literature relates to the anterior maxilla, where the labial bone thickness is thin. However, Theye et al [56] measured the bony dimensions at first molar sites and found that 20.8% of mandibular and 62.18% of maxillary first molars have a buccal cortical wall of less than 1 mm thick.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the afore mentioned literature relates to the anterior maxilla, where the labial bone thickness is thin. However, Theye et al [56] measured the bony dimensions at first molar sites and found that 20.8% of mandibular and 62.18% of maxillary first molars have a buccal cortical wall of less than 1 mm thick.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, the molar socket anatomy is complex and primary stability is often difficult to achieve, even with normal wide diameter implants. Theye et al used micro CT to measure the dimensions of molar sockets and reported a mean width of 8.80 mm for the mandibular and 7.05 mm for the maxillary molars in the mesio‐distal direction, and in the buccolingual direction 7.24 mm and 11.58 mm for the mandibular and maxillary molars respectively.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 As discussed earlier, the molar socket anatomy is complex and primary stability is often difficult to achieve, even with normal wide diameter implants. Theye et al 16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations